Прогнозування конкурентоспроможності продукції за сукупністю показників якості на основі нейромережного моделювання - Fedin, S. S.; Zubretska, N. A.; Goncharov, A. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
On the basis of formalization the problem of spatial extrapolation in neural network logical basis the approach to creation neural network models of forecasting of different purpose products competitiveness is offered. The neural network model of expert system for assessment and forecasting of competitiveness of the products by the totality of single indicators of quality and price is developed. The practical implementation of model is carried out on the example of the household refrigerators.